Ethnobotanical Diversity of Cassava (Manihot esculenta Crantz) in the Peruvian Amazon - Stephen P. Wooding; Christian Nolorbe Payahua (Diversity, 2022)
Cassava is a key tropical crop that serves as a major source of nutrition throughout equatorial South America, Africa, and Asia. Genetic and paleoethnobotanical findings indicate that it was first domesticated on the southern margin of Amazonia ~10,000 years ago. However, anthropogenic processes underlying its subsequent diversification remain unclear. To shed light on them, we investigated agricultural practices and phenotypic variation in cassava on the upper Amazon River, in Loreto, Perú. We interviewed subsistence growers on five Amazon tributaries and collected data on the husbandry, morphology, and nutritional composition of their crops. We found 45 distinct cultivars. Many of their morphological features, such as stature and leaf dimensions, exhibited expected phenotype–phenotype associations. However, starch content showed no association with any other phenotype (mean p = 0.57), suggesting it has been under selective pressure exerted by growers. In addition, all cultivars’ tubers had cyanide content under 25 ppm, a low level of toxicity by global standards. Evidence of sexual reproduction and cultivar hybridization was common and a probable source of new variation. However, cultivars from different rivers showed little evidence of differentiation, possibly as the result of human transport. Thus, human influences in the region simultaneously enhance and constrain variability in the crop.